Speaking for IELTS - Kovacs, Karen E. (Karen Elizabeth), 1961- (Collins English for exams., 2019)
If your speaking is preventing you from getting the score you need in IELTS, Collins Speaking for IELTS can help. Don't let one skill hold you back. Collins Speaking for IELTS has been specially created for learners of English who plan to take the IELTS exam to demonstrate that they have the required ability to communicate effectively in English, either at work or at university. It is ideal for learners with band score 5 - 5.5 who are aiming for band score 6 or higher on the IELTS test (CEF level B1 and above). This major new edition has been thoroughly updated and improved to make it even easier to use. Now in full colour, the book has a new layout and a series of brand new features to help students feel fully prepared for their IELTS exam: Enhanced answer keys with further explanations of why answers are right or wrong, or ambiguous; 'Watch out!' boxes that highlight common IELTS mistakes; A revision checklist at the end of each section to remind students what they should do for each particular part of the exam. What is IELTS?The International English Language Testing System (IELTS) is the most common test used by universities for foreign students to prove their language level. IELTS is also increasingly used for immigration purposes, with many countries requiring visa applicants whose first language is not English to submit an IELTS grade. The system tests candidates' Reading, Writing, Listening and Speaking in four separate papers. Usually, students must gain a good mark in all four skills in order to gain entry to the course, job, or country of their choice. For this reason, candidates will often sit the exam numerous times to secure the score that they need. Powered by COBUILD. The 4-billion-word Collins corpus is the world's largest database of the English language. It is updated every month and has been at the heart of Collins COBUILD for more than 30 years.